The dark sides of environmental requirement in a supply chain with information asymmetry. (March 2021) - Zhang, Pan; Xiong, Yu; Zhou, Yu
Highlights: An eco-friendly retailer does not have the supplier's environmental information. An analytical model is developed to design information screening contracts. A cut-off policy can induce the supplier to report its private information. Double marginalization might can be moderated by the asymmetric information. Two-part tariff contract can lead to a win-win situation. Abstract: Consumers' environmental awareness imposes pressures on retailers' procurement and induces powerful retailers to make environmental requirement on their supplier's products. However, retailers' desire for procuring eco-friendly products is usually impeded by their supplier's asymmetric environmental information. We, therefore, develop an analytical framework to design information screening contracts and investigate which contract is more efficient in stimulating suppliers' environmental innovation. Meanwhile, we examine whether the retailer's environmental requirement could achieve the desired results, e.g., improving the products' greenness and its own profit. We consider two forms of contract menu, i.e., a two-part tariff contract (TT contract) and an innovation effort requirement contract (IER contract), and our analysis indicates that both contracts can induce the supplier to report its private information. Moreover, the double marginalization effect in the supply chain could be moderated by the asymmetric information under certain conditions. We also find that the IER contract dominates the TT contract under certain conditions. Comment wisdom might suggest that the IER contract will result in a higher environmental innovation level. However, our analysis demonstrates that the opposite conclusion, i.e., the IER contract results in a lower environmental innovation level. Through numerical analysis, we further find that the IER can lead to a lower profit of the retailer and a worse supply chain performance. These negative impacts of the IER contract are referred to as the dark sides of environmental requirement in the supply chain with information asymmetry.